The Influence of Innovative Leadership and Information Technology Competence, through Organizational Transformation, on EMIS User Satisfaction - Maulida Annisa Lubis; Muhammad Ilham (Journal of Educational Management Research, 2026)
The development of information technology in the digital era makes educational information systems a strategic necessity to improve service quality, accelerate administrative processes, and support decision-making. Although EMIS has been implemented in madrasas, many users face obstacles such as limited digital competency and resistance to technological change, resulting in suboptimal user satisfaction. This study aims to analyze the influence of innovative leadership and IT competency on EMIS user satisfaction, with organizational transformation as a mediator. The study used a quantitative approach with a descriptive survey design in Madrasas, involving 90 respondents through total sampling. Data were collected using questionnaires, observations, and document reviews, then analyzed using SEM-PLS to test direct and indirect relationships between variables. The results show that innovative leadership and IT competency play an important role in driving organizational transformation, which in turn increases EMIS user satisfaction. This study emphasizes the importance of integrating leadership, technical capabilities, and organizational transformation, and provides theoretical contributions to the development of a technology-based educational structural model and practical guidance for educational institutions.